2018
DOI: 10.1016/j.quascirev.2018.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Asian summer monsoons to idealized precession and obliquity forcing in a set of GCMs

Abstract: This is a repository copy of Response of the Asian summer monsoons to idealized precession and obliquity forcing in a set of GCMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 66 publications
7
68
2
Order By: Relevance
“…However, the change of regional precipitation patterns may not be the same as the orbital variations. For example, Pausata et al (2011) simulated climate during the Heinrich events and found no obvious precipitation changes in China, while our study and other simulations (Bosmans et al, 2018) for orbital forcing show substantial precipitation changes in China. There are already studies showing the coherency of Asian speleothem 18 O vanishes at scales shorter than millennial (Chu et al, 2012;Li et al, 2014;Wan et al, 2011;Zhang et al, 2019), and further investigations are needed to identify at which time scales the coherency disappears.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, the change of regional precipitation patterns may not be the same as the orbital variations. For example, Pausata et al (2011) simulated climate during the Heinrich events and found no obvious precipitation changes in China, while our study and other simulations (Bosmans et al, 2018) for orbital forcing show substantial precipitation changes in China. There are already studies showing the coherency of Asian speleothem 18 O vanishes at scales shorter than millennial (Chu et al, 2012;Li et al, 2014;Wan et al, 2011;Zhang et al, 2019), and further investigations are needed to identify at which time scales the coherency disappears.…”
Section: Discussioncontrasting
confidence: 66%
“…Speleothem trace element ratios also suggest that low values of speleothem δ 18 O in central China can coincide with dryness instead of wetness in that region (Zhang et al, ). This, however, is not enough to reach a conclusion regarding central China receiving less precipitation in P min , since similar simulations with other models like EC‐Earth and GFDL‐CM2.1 do not clearly show less precipitation in central China (Bosmans et al, ). These models all show a northward migration of the East Asian monsoon circulation.…”
Section: Resultsmentioning
confidence: 79%
“…The increases in precipitation over the Indian ocean during summer follow a 'warmergets-wetter' pattern (Xie et al, 2010;Huang et al, 2013), whereby SST patterns are the dominant mechanism for tropical precipitation response in areas where local warming in SSTs exceeds the tropical average (Xie et al, 2014). The results presented for orbital configurations specific to the individual interglacial events studied are supported by more idealised orbital forcing experiments completed by Bosmans et al (2018).…”
Section: How Does Hadcm3 Simulate the Indian Monsoon In The Pliocene mentioning
confidence: 53%
“…S10 and S11). Models with different levels of complexities: QTCM (Hsu et al, 2010), Quasi-geostrophic model EC-Bilt (Tuenter et al, 2003), GCM with slab ocean (Battisti et al, 2014) and finally the fully coupled model EC-Earth (Bosmans et al, 2018) have all shown a shift in precipitation between land and ocean, when subjected to the precessional forcing. However, there are no proxies for precipitation over oceans to verify this.…”
Section: Discussionmentioning
confidence: 99%